Periapical radiography using bisect technique in autistic children through nonpharmacological approach: a case report - Yohanes Hutasoit; Ria N. Firman; Arlette Suzy (DiscoverSys Inc., 2017)
Objective:The periapical dental radiography using bisect technique needs a special skill in managing autistic patient. Autism is one of the characteristics from handicapped children with behavioral syndrome caused by neurological disturbance characterized by behavioral disturbance, communication, and social interaction difficulties occurringin the first three years of the children life.Problems occurringin dental radiography in such children make the bisect technique necessary. Dentist and the operator need to do special preparations to optimally create the dental radiograph using two approaches, i.e. nonpharmacological and pharmacological approaches.Methods:In this case, dental imaging using bisect technique for autistic children is performed using modified technique for periapical and occlusal imaging as well as nonpharmacological approach.Result:Theradiograph examination for autistic children using modified technique can be done successfully.Conclusion:Dental radiographin autistic children canbe performed by modifying periapical radiograph using bisecting technique with nonpharmacological approach.